Which is the most effective rescue treatment after the failure of mechanical thrombectomy for acute basilar artery occlusion? - Luo, Jun; Wu, Deping; Li, Zhimin; Xie, Dongjing; Huang, Jiacheng; Song, Jiaxing; Luo, Weidong; Liu, Shuai; Li, Fengli; Zi, Wenjie; Huang, Qiaojuan; Luo, Jiefeng; et al. (Frontiers in Neurology, 2022)
Objective: To evaluate the effectiveness and safety of rescue therapy and to investigate which rescue measure was the best choice for acute basilar artery occlusion (BAO) after failure of mechanical thrombectomy (MT). Methods: We recruited patients from BASILAR registry. All participants were divided into recanalized with or without rescue therapy group and nonrecanalized group. clinical outcomes at 90 days and 1 year were compared. Association of rescue measures with favorable outcomes (modified Rankin Scale score [mRS] 0-3) in patients achieving successful recanalization with rescue therapy was estimated with multivariate logistic regression analyses. Results: There were 112 patients with failure recanalization and 473 patients with successful recanalization which included 218 patients receiving rescue therapy and 255 patients without rescue therapy. Of these, 111 (43.5%) patients in recanalized without rescue therapy group achieved favorable outcomes at 90 days, 65 (29.8%) patients in recanalized with rescue therapy group, and 9 (8.0%) patients in nonrecanalized group. Recanalization with or without rescue therapy were associated with favorable outcomes both at 90 days and 1 year compared with nonrecanalized group. Moreover, Wingspan stents, Apollo stents, and balloon angioplasty were associated with higher rates of favorable outcomes at 90 days and 1 year than Solitaire stents in patients receiving rescue therapy. Conclusions Whether rescue therapy or not, recanalization leads to favorable outcomes for patients with acute BAO. Balloon angioplasty, Wingspan stenting or Apollo stenting might be effective and safe choices but Solitaire stent was not recommended as rescue implant stents for acute BAO after MT failure.